ELEMEN ELEMEN BRAND EQUITY YANG MEMBEDAKAN PRODUK OLAHRAGA MEREK ADIDAS DENGAN NIKE DI KOTA DENPASAR - Widiananta, Kadek Tresna; Wardana, Made (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the difference in Brand Equity’s elements on brand Adidas with Nike in Denpasar. The population in this study are all people in Denpasar who use the product brand Adidas and Nike. The samples that used in this study is 100. The sampling technique which used was purposive sampling. Methods of data collection in this research is participant observation. The method which used is different T test with SPSS 21.0 for windows. Results showed that there are significant difference between the three elements of Brand Equity from Adidas and Nike.They are brand awareness, brand association, perceived quality, but the brand loyalty shown no significant difference.
Keywords: Brand, Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty.